2011
DOI: 10.1089/brain.2011.0016
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Resting-State Functional Connectivity in Early Human Immunodeficiency Virus Infection

Abstract: Limited information is available concerning changes that occur in the brain early in human immunodeficiency virus (HIV) infection. This investigation evaluated resting-state functional connectivity, which is based on correlations of spontaneous blood oxygen level-dependent functional magnetic resonance imaging (fMRI) oscillations between brain regions, in 15 subjects within the first year of HIV infection and in 15 age-matched controls. Resting-state fMRI data for each session were concatenated in time across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 64 publications
10
82
2
Order By: Relevance
“…While a recent study of functional connectivity in HIV + individuals suggested altered occipital lobe connectivity (Wang et al, 2011), in our older cohort, cortical connectivity was…”
Section: Discussioncontrasting
confidence: 82%
“…While a recent study of functional connectivity in HIV + individuals suggested altered occipital lobe connectivity (Wang et al, 2011), in our older cohort, cortical connectivity was…”
Section: Discussioncontrasting
confidence: 82%
“…The resulting estimated component maps were divided by the standard deviation of the residual noise and thresholded at a posteriori probability threshold of p > .5 (i.e., an equal loss is placed on false positives and false negatives) by fitting a Gaussian/gamma mixture model to the histogram of intensity values [20] . The number of components was set to 34 as it seems to be a good trade-off to get a sufficient number of relevant networks (around ten) without splitting them into subcomponents [21] . The most relevant RSNs were then selected, by first discarding the components with very high power (more than a third of the total power) in high-frequency range ( > 0.1 Hz) of their spectrum; and then using an in-house 'goodness-of-fit' MatLab function upon the 10 RSN map templates from Smith et al [22] .…”
Section: Resting-state Ica Time-series Extractionmentioning
confidence: 99%
“…• Human Immunodeficiency Virus Infection (HIV): The second dataset is collected from the Chicago Early HIV Infection Study in Northwestern University [15]. The dataset contains fMRI brain images of patients with early HIV infection (morbid) as well as normal controls (healthy).…”
Section: Evaluation On Cglasso • Datasetmentioning
confidence: 99%